Analysis of 5,8,11,14,17-Eicosapentaenoic Acid and 4,7,10,13,16,19-Docosahexaenoic Acid in the Viscera of Marine Organisms Using Gas Chromatography - Zhang, Deyong; Xu, Xiaolu; Shen, Xiu-Ying; Xu, Huiying (Asian Journal of Chemistry, 2015)
A gas chromatography was established for analysis of 5,8,11,14,17-eicosapentaenoic acid and 4,7,10,13,16,19-docosahexaenoic acid in the viscera of marine organisms. The viscera of 6 kinds of non-fish marine organisms were then collected for oil extraction and detection of 4,7,10,13,16,19-docosahexaenoic acid and 5,8,11,14,17-eicosapentaenoic acid. The oil extraction ratio varied from 0.72 to 6.23 % (wt. %). Scylla serrata presented the highest oil yield, followed by Architeuthis dux and Panopea abrupta. The 5,8,11,14,17-eicosapentaenoic acid concentration (in methyl ester form) in the oil varied from 0.56 to 7.75 (mg/g). Scylla serrata presented the highest 5,8,11,14,17-eicosapentaenoic acid concentration (p < 0.05), followed by Architeuthis dux and Panopea abrupta. The 4,7,10,13,16,19-docosahexaenoic acid concentration(in methyl ester form) varied from 0.15 to 4.71 (mg/g). Architeuthis dux and Scylla serrata presented obviously higher 4,7,10,13,16,19-docosahexaenoic acid concentration than other species (p < 0.05).